The policy of AMB journal editors / Uredniška politika AMB revije - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
The Faculty of Medicine, University of Maribor, (MF UM) founded its own scientific journal, Acta Medico-Biotechnica (AMB), in December 2008. This was the first time in Slovenia that a medical faculty has founded a medical journal. The AMB was the result of the personal effort and enthusiasm of the Dean of MF UM, Prof. Dr. Ivan Krajnc, Dr. Med., and his co-workers, especially the members of the editorial board. Coming from a small country such as Slovenia, we began as one of a large number of “peripheral” journals. However, we knew that our colleagues were undertaking very important scientific work but did not always the opportunity to present their data to the global medical community. As editors, one of our goals is to maintain an authorhelpful approach. This involves good cooperation with the contributors to help increase their awareness of the importance of their research work, follow the recommendations of experienced peer reviewers, learn more about writing a scientific paper, and be encouraged to write and submit the paper not only to AMB but also to other scientific journals. The time required to review a manuscript is very important.We are proud to announce that after one year the Journal’s content is freely available on the MF UM website www.actamedbio.uni-mb.si, so its quality can be judged not only by the local community but also by international readers.What are our goals for the future? At the moment we publish two issues per year, but we aim to publish extra theme issues on different interesting topics such are e-learning, telemedicine, public health and aging.One of our next goals is to stimulate medical students to undertake research. Every year our medical students compete for the Dean’s Award. The prize is awarded on faculty day in December every year. Last year we evaluated 9 research papers and this year 7 papers were submitted. Despite the small number of our students, there is huge interest in research. We must intensify our cooperation with mentors to encourage students to write papers and to submit them for peer review. AMB wants to publish the majority of the students’ research work either in regular issues or special annual students’ AMB issues, depending on the number and quality of the articles. One paper (Stana J, Stropnik D, et al. AMB 2009; 1: 61-7) has already been published.Additionally, the editors encourage postgraduate students to publish part of their doctoral research in AMB. Our next goal is to contribute to continuing medical education, especially with review articles invited by the editor.In future, we hope to present selected abstracts of publications from our MF UM teachers and collaborators in indexed journals in the section Faculty of Medicine University of Maribor international publications.We sincerely hope that over the years AMB will become internationally visible, such as by being included in the MEDLINE/Pubmed, ISI (Thompson Scientific Database Current Contents/Clinical Medicine and Science Citation Index Expanded).Overall, the main editorial goal remains the development of a high quality journal, regularly published and subject to international peer review.We are aware that AMB will remain a “peripheral” journal. Nevertheless the mission of AMB is much more than to produce scientific content. It should contribute to the promotion of the Faculty of Medicine and University of Maribor and support and encourage local research.Last but not least, the editors wish to warmly thank all the authors and reviewers for their cooperation and their enthusiasm, which has helped our young AMB journal grow and evolve.Omnia rerum principia parva sunt.The beginnings of all the things are small.(Cicero)Dušica PahorEditor-in-chief (Cicero) Du{ica Pahor Editor-in-chief
Keywords: Acta medico-biotechnica; uredniška politika